2009
DOI: 10.1590/s0103-90162009000400007
|View full text |Cite
|
Sign up to set email alerts
|

Honey bee as an effective pollinating agent of pumpkin

Abstract: The production of fruits and seeds of many crops is increased when bees visit their flowers pollinating them. The aim of this research was to study the pollination of pumpkins (Cucurbita maxima Duch. var. Exposição), to determine the diversity of insects visiting its flowers, the time and type of provision obtained and the effect of the visits on fruit set, fruit size and weight, and number of seeds. Apis mellifera L. accounted for 73.4% of the visits made by bees, collecting pollen during 34.5 s per flower an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 4 publications
2
23
0
4
Order By: Relevance
“…In an assessment of the importance of bees for Aodai cucumber production, Nogueira- Couto and Calmona (1993) concluded that honey bees facilitate cucumber fruit set due to their visits to the flowers, thus promoting pollination. Africanized bees can efficiently pollinate several species of the genus Cucurbita (FREE, 1993;NICODEMO et al, 2009, VIDAL et al, 2010.…”
Section: Resultsmentioning
confidence: 99%
“…In an assessment of the importance of bees for Aodai cucumber production, Nogueira- Couto and Calmona (1993) concluded that honey bees facilitate cucumber fruit set due to their visits to the flowers, thus promoting pollination. Africanized bees can efficiently pollinate several species of the genus Cucurbita (FREE, 1993;NICODEMO et al, 2009, VIDAL et al, 2010.…”
Section: Resultsmentioning
confidence: 99%
“…mean weight of the fruit was less than 300 g. Excess visitation can induce the bees to remove pollen grains that have been deposited on the stigmas, whether intentional or not, as was found in a field experiment involving pollination of pumpkin (Cucurbita maxima) in an area with 1,200 m² of plantings and 30 colonies of honey bees (Nicodemo et al, 2009).…”
Section: Period Of Availability Of Flowers To Visitation Of Beesmentioning
confidence: 91%
“…Stephenson et al (1988) found lower fruit set, fruit growth rate and fruit size in zucchini, from flowers treated with low and medium pollen load (240 and 480 pollen grains) than the fruits resulting from flowers with high pollen load or free visitation. Nicodemo et al (2009) reached highest fruit set level when the number of visit by Apis mellifera was 16 per female flower of pumpkin. Although pumpkin fruit set will occur with natural pollinators, the addition of honey bee colonies will ensure the presence of pollinators, to maximize fruit size (Walters & Taylor 2006) The specific objectives of this work were: (a) determine the amount of pollen removed from anthers after different number of bee visits and the amount of pollen collected per bee at different periods of the day; (b) Estimate the number of pollen grains deposited on the stigma by honey bees; (c) Relate pollination and fruit set of the pumpkin to pollen load on the stigma, and (d) evaluate the influence of the male flower nectary's opening on the flower's attractiveness to honey bees.…”
Section: Introductionmentioning
confidence: 99%